2020
DOI: 10.1371/journal.pone.0240890
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drug use and HIV drug resistance in female sex workers in Tanzania and the Dominican Republic

Abstract: Objective Female sex workers (FSW) have increased risk of HIV infection. Antiretroviral treatment (ART) can improve HIV outcomes and prevent HIV transmission. We analyzed antiretroviral (ARV) drug use and HIV drug resistance among HIV-positive FSW in the Dominican Republic and Tanzania. Methods Plasma samples collected at study entry with viral loads >1,000 copies/mL were tested for ARV drugs and HIV drug resistance. ARV drug testing was performed using a qualitative as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Patients who are on second-line regimens are more likely to be at risk for virologic failure due to existing difficulties with ART adherence and possibly undiagnosed drug resistance. 22 24 Other contributing factors include the greater pill burden, more complicated dosing schedules, and higher rates of adverse effects known to be associated with PI-based regimens. 25 , 26 Access to genotype testing is limited for PWH in the DR, and ART regimens are frequently changed based on HIV disease progression, lack of viral suppression and the availability of medications in the hospital pharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who are on second-line regimens are more likely to be at risk for virologic failure due to existing difficulties with ART adherence and possibly undiagnosed drug resistance. 22 24 Other contributing factors include the greater pill burden, more complicated dosing schedules, and higher rates of adverse effects known to be associated with PI-based regimens. 25 , 26 Access to genotype testing is limited for PWH in the DR, and ART regimens are frequently changed based on HIV disease progression, lack of viral suppression and the availability of medications in the hospital pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of virologic failure to certain ART regimens due to drug resistance is unknown, though one small study detected at least one antiretroviral class mutation in 54% of samples from the DR, with 24% of patients having multi-class resistance. 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O maior tempo de convívio com a infecção pode facilitar o conhecimento acerca da importânica da adesão medicamentosa, para supressão virológica do HIV (14) . Por outro lado, a cronificação do tratamento dificulta a adesão ao longo dos anos, pela probabilidade da resistência aos medicamentos e pela necessidade de tomada diária dos remédios (15) .…”
Section: Discussionunclassified
“…Women represent more than half of the adults living with HIV in the DR, in comparison to Latin America where men are overrepresented in the proportion of PLHIV [ 21 ]. A study with PLHIV engaged in sex work in the DR and Tanzania found many women had not achieved viral suppression, had high rates of HIV drug resistance, and suboptimal ART adherence [ 22 ].…”
Section: Introductionmentioning
confidence: 99%